Building a Strong Organizational Culture: Development and Implementation of Values in the Islamic University of Kadiri - Kurniawati, Endah; Ayuanti, Rafikhein Novia (JMK (Jurnal Manajemen dan Kewirausahaan), 2024)
This research explores the creation of organizational culture at Islamic University of Kadiri, focusing on the development and implementation of core values. The background of this study is based on the premise that a strong organizational culture improves the performance and morality of the institution. Objective of research: to know the process of development of organizational values, implementation and their impact on organizational culture at Islamic University of Kadiri. Data sources: primary and secondary data, as well as thematic analysis to generate comprehensive insights into cultural dynamics at Islamic University of Kadiri. Research results show that the university upholds values such as integrity, respect, and collaboration. However, the study also reveals the need for a more structured programme to effectively implant and strengthen these values. The significance of this study lies in its contribution to understanding the mechanisms through which values can be systematically integrated into the culture of educational institutions, which potentially become a blueprint for other universities who want to build a strong and effective organizational culture. It not only improves the ethical dimension of the institution, but also the overall academic and administrative effectiveness.